BrAIn Jam: neural signal-informed adaptive system for drumming collaboration with an AI-driven virtual musician - Hopkins, Torin; Sun, Ruojia; Chuan Weng, Suibi Che; Ma, Shih-Yu; Crum, James; Hirshfield, Leanne; Do, Ellen Yi-Luen (Frontiers in Computer Science, 2025)
Collaboration between improvising musicians requires a dynamic exchange of subtleties in human musical communication. Many musicians can intuit this information, however, translating this knowledge to embodied computer-driven musicianship systems—be they robotic or virtual musicians—remains an ongoing challenge. Methods of communicating musical information to computer-driven musicianship systems have traditionally been accomplished using an array of sensing techniques such as MIDI, audio, and video. However, utilizing musical information from the human brain has only been explored in limited social and musical contexts. This paper presents “BrAIn Jam,” utilizing functional near-infrared spectroscopy to monitor human drummers' brain states during musical collaboration with an AI-driven virtual musician. Our system includes a real-time algorithm for preprocessing and classifying brain data, enabling dynamic AI rhythm adjustments based on neural signal processing. Our formative study is conducted in two phases: (1) training individualized machine learning models using data collected during a controlled experiment, and (2) using these models to inform an embodied AI-driven virtual musician in a real-time improvised drumming collaboration. In this paper, we discuss our experimental approach to isolating a network of brain areas involved in music improvisation with embodied AI-driven musicians, a comparative analysis of several machine learning models, and post hoc analysis of brain activation to corroborate our findings. We then synthesize findings from interviews with our participants and report on the challenges and opportunities for designing music systems with functional near-infrared spectroscopy, as well as the applicability of other physiological sensing techniques for human and AI-driven musician communication.